Management of primary dysmenorrhea in young women with frameless LNG-IUS - Wildemeersch D; Jandi S; Pett A; Hasskamp T (Dove Medical Press, 2014)
Dirk Wildemeersch,1 Sohela Jandi,2 Ansgar Pett,2 Thomas Hasskamp3 1Gynecological Outpatient Clinic and IUD Training Center, Ghent, Belgium; 2Gynecological Outpatient Clinic, Berlin, Germany; 3GynMünster, Münster, Germany Abstract: The objective of this paper is to discuss the potential advantages of intrauterine treatment with a frameless levonorgestrel (LNG)-releasing intrauterine system (IUS) in young women presenting with primary dysmenorrhea associated with heavy menstrual bleeding. The paper is based on clinical reports of 21 cases of primary and secondary dysmenorrhea treated with the frameless LNG-IUS. Three typical examples of young women between 16 and 20 years of age, who presented with moderate-to-severe primary dysmenorrhea associated with heavy menstrual bleeding, are presented as examples. Following pelvic examination, including vaginal sonography, a frameless LNG-IUS, releasing 20 µg of LNG/day, was inserted. The three patients developed amenorrhea, or scanty menstrual bleeding, and absence of pain complaints within a few months. We conclude that continuous, intrauterine progestogen delivery could be a treatment of choice of this inconvenient condition. In addition, the good experiences with the frameless LNG-IUS in other studies suggests that the frameless design may be preferred over a framed LNG-IUS, as the absence of a frame, resulting in optimal tolerance, is particularly advantageous in these women. Keywords: heavy menstrual bleeding, contraception, FibroPlant, intrauterine system